Antirabic vaccination accident in cattle (Flury strain) - Silva, Renato Augusto da; Passos, Jalmyr Joaquim dos (Pesquisa Agropecuaria Brasileira, 2024)
The authors studied an antirabic vaccination accident on a Zebu cattle breeding farm in the former Distrito Federal, to day State of Guanabara. The cattle had been vaccinated with avianized rabies vaccine elaborated with modified rabic virus (Flury strain), low egg passage. There were vaccinated 483 bovines and 26 horses. Of these, 52 bovines got sick, of which 39 died and 13 recovered. Post-mortem examinations were performed on 29 animals. Inoculation of brain and cervical spinal cord suspensions intracerebrally were made in adult and baby mice, and 17 strains of rabic virus were isolated. One of these isolated strains (material 1.330) was pathogenic for rabbits, guinea-pigs and hamsters, which had been inoculated intramuscularly and intracerebrally. The titer of the virus strain in baby and adult mice was 10-3.50 LD50 by intracerebral route, with 0.03 ml. This virus strain grew well in seven days old chick-embryo, when inoculated by yolk-sac route. The vaccine, which caused the accident, was also inoculated in laboratory animals. The vaccine contained low egg passage virus. The vaccine was lethal for baby and adult mice, rabbits and guinea-pigs, which had been inoculated intracerebrally and intramuscularly. They died showing rabic symptoms. Ten blood samples collected at the onset of the disease were inoculated in mice. No virus could be shown in the circulating blood. The identification of the isolated agent was determined by the serum-neutralization test and by its ability to grow well in chick-embryo. This indicates a modified rabic virus.